"One ruler measures to the end": Rule hardening in grassroots governance – taking a pilot project in urban renewal as an example. (January 2021) - Shi, Yunqing
Regarding launching an urban renewal project, rising social pressure makes the grassroots state harden the rules while the remaining high pressure from the top makes them keep rules elastic, the contradiction between which causes a dilemma in urban development nowadays. Taking a landmark pilot project as an example, via the observation of the practice of the rule-hardening principle described as "one ruler measures to the end", this article tries to answer the question of how it is possible for power to reproduce its operational space under recently rising regulatory constraints. In this case, the principle of "rule hardening" includes both "results" and "process" and is fulfilled through a three-step mechanism of hardening in external conditions, hardening in compromising rules and hardening in the limitation of introducing pressure. Through this mechanism, the grassroots state manages to mobilize the resources embedded in the system and extend the hidden boundaries of the hard and rigorous rules on the surface that make the rules elastic and soft again, but in a more formal institutional and organizational way. This could be considered the state's response to the rising social protests during the last phase and indicates a more subtle and less obvious manner of governance, which shows the continuous interaction between the state and the society in the long view of history.